Acute kidney injury requiring renal replacement therapy during the COVID-19 pandemic: what are our options for treating it in Latin America? - Rizo-Topete, Lilia M. (2021)
Division of Nephrology Universidad Autónoma de Nuevo León Hospital Universitario “José Eleuterio González”